2004
DOI: 10.1080/15021149.2004.11434227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Video Modelling on Training and Generalisation of Social Initiation and Reciprocal Play by Children With Autism

Abstract: Previous research using children with autism has shown that video modelling can be effective in enhancing a variety of skills. The present study was conducted to assess the effectiveness of video modelling intervention to promote social initiation and reciprocal play as well as to increase the likelihood of generalisation of the treatment gains across stimuli. Three children with autism participated in this study and experimental control was demonstrated using a multiple baseline across subjects design. Each c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…To date, a number of advanced technologies have targeted the training of social competence of children with ASD [13], including video modeling [19], virtual reality [20] and socially assistive robots [6]. Yet, there is still a lack of well-established practices for the design of technology to support therapeutic and educational interventions for these children [7].…”
Section: Introductionmentioning
confidence: 99%
“…To date, a number of advanced technologies have targeted the training of social competence of children with ASD [13], including video modeling [19], virtual reality [20] and socially assistive robots [6]. Yet, there is still a lack of well-established practices for the design of technology to support therapeutic and educational interventions for these children [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the video display could have served as a verbal discriminative stimulus that affected the subsequent responding of the children and video modeling could be examined as an example of rule-governed behavior. It is also worth mentioning that although language development was not included in the objectives of any of the studies by Keenan (2004a &2004b) all participants began imitating the verbal components presented on the video. Interestingly, video modeling in these two studies produced quicker changes in the This article is a version after peer-review, with revisions having been made (i.e., pre-publication version).…”
Section: Theoretical Issuesmentioning
confidence: 99%
“…The overall objective of the first study (Nikopoulos & Keenan, 2004a) was to examine a) whether a video modeling intervention could be effective in promoting social play skills (i.e., social initiation & reciprocal play) in a simplified environment (i.e., in the presence of only one toy at a time) and b) whether potential success with one toy during video modeling training could increase the probability of success with new toys in the absence of video (i.e., generalization of social play).…”
Section: Empirical Validation Of Video Modeling To Support Generalizamentioning
confidence: 99%
“…To date, a number of advanced technologies have targeted the training of social competence of children with ASD [10] including video modeling [11] virtual reality [12] and socially assistive robots [13]. Recent studies have shown that individuals can learn to cope with common social situations if they are made to enact possible scenarios they may encounter in real life.…”
Section: Difficulty With Social Imaginationmentioning
confidence: 99%